Burden of disease attributable to high body mass index in Belgium: a comparative risk assessment analysis - Stefanie Vandevijvere; Delphine De Smedt; Brecht Devleesschauwer; Robby De Pauw; Johan Van der Heyden; Sarah Nayani; Vanessa Gorasso; Wilma Johanna Nusselder; Henk Hilderink (BMJ Public Health)
Background and methods High body mass index (BMI) is a major risk factor for several non-communicable diseases. The increasing concern about the health and economic burden of BMI makes it essential for countries to track their progress on major modifiable risk exposures. The aim of the study is to estimate the burden attributable to high BMI in Belgium, in terms of years of life lost due to disability (YLD), years of life lost due to premature mortality (YLL) and disease costs, using comparative risk assessment. We followed the general framework established in the Global Burden of Diseases, Injuries and Risk Factors study. Population attributable fractions were calculated for the year 2018 for selected health outcomes using local estimates of BMI and burden of disease estimates from the Belgian Burden of Disease study.Results According to our figures, around 37 800 YLD, 56 000 YLL and €1.85 billion in healthcare costs can be attributed to a high BMI. Diabetes had the highest number of YLD attributable to high BMI followed by musculoskeletal disorders. Cardiovascular diseases accounted for the highest burden in terms of YLL attributable to high BMI, followed by diabetes and different forms of cancers (i.e., breast, colon and rectum and oesophageal cancer).Conclusion A substantial proportion of the burden of disease could be prevented when reducing BMI in Belgium. This evidence on the impact of risk factors is important for monitoring disease burdens and setting priorities for health prevention policies.